PENGGUNAAN LEMBAR KERJA MAHASISWA TERBIMBING BERBASIS INQUIRY PADA MATA KULIAH PENINGKATAN KETERAMPILAN BERBAHASA INDONESIA (PKBI) UNTUK MENGEMBANGKAN KARAKTER MAHASISWA PGSD IKIP PGRI MADIUN - Dewi Tryanasari (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2011)
Every teacher must foster the positive attitude, all the more, those of elementary schools. This kind of positive attitude should be cultivated since they are still studying in the teacher training study program. The students of elementary school teacher training study program of IKIP PGRI MADIUN have not yet coped with the positive attitude well, which is shown through evidence that they have not yet foster self-discipline in many class activities, such as being late getting in class, being incomplete doing tasks, being insensitive against the environmental changes and phenomena. In effort of cultivating their positive mental attitude, this research is conducted in the form of class action research design by inquiry-based controlled student worksheet. The student worksheet is used to develop the inquiry learning process for the mental attitude development, and the lecturer’s control is used to develop the linguistic and to nurture the concepts. As the nature of classroom action researh is to overcome problems, this research is conduted for the most problematic class of all, i.e. class 2G. The analysis results in conclusions that the positive attitude of the students develops in terms of self-discipline and learning activity, so as to suggest that inquiry-based controlled student worksheet is effective to develop students mental attitude.